Do genome‐scale models need exact solvers or clearer standards? - Ali Ebrahim; Eivind Almaas; Eugen Bauer; Aarash Bordbar; Anthony P Burgard; Roger L Chang; Andreas Dräger; Iman Famili; Adam M Feist; Ronan MT Fleming; Stephen S Fong; Vassily Hatzimanikatis; et al. (Molecular Systems Biology)
Graphical Abstract Recent results obtained by Chindelevitch et al (2014) are challenged by Ebrahim et al, illustrating several issues in the reproducibility of computational biology methods.